2020
DOI: 10.3390/antibiotics9120893
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Various Streptococcus spp. and Their Antimicrobial Resistance Patterns in Clinical Specimens from Austrian Swine Stocks

Abstract: Knowledge of pathogenic potential, frequency and antimicrobial resistance patterns of porcine Streptococcus (S.) spp. other than S. suis is scarce. Between 2016 and 2020, altogether 553 S. spp. isolates were recovered from clinical specimens taken from Austrian swine stocks and submitted for routine microbiological examination. Antimicrobial susceptibility testing towards eight antimicrobial substances was performed using disk diffusion test. All isolates from skin lesions belonged to the species S. dysgalacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
2
9
0
5
Order By: Relevance
“…Similar resistance patterns have also been reported in studies in Austria, where tetracycline resistance was reported among 66% of Streptococcus suis isolates (increasing up to 88% of Sc. suis isolates obtained from joints) and 67.7% of Escherichia coli isolates obtained from piglets with diarrhoea [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar resistance patterns have also been reported in studies in Austria, where tetracycline resistance was reported among 66% of Streptococcus suis isolates (increasing up to 88% of Sc. suis isolates obtained from joints) and 67.7% of Escherichia coli isolates obtained from piglets with diarrhoea [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, the blood cultures that were grown before antibiotic use revealed the presence of S . thoraltensis , a novel opportunistic pathogen that colonizes the upper respiratory tract and belongs to the alpha‐hemolytic Streptococcus genus 9 . The localized inflammatory response of the sphenoid sinus could lead to colonizing bacterial invasion of the bloodstream, resulting in transient bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…and Streptococcus spp. (25)(26)(27). Inoculated plates were incubated for 48 h at 37 • C under standard atmospheric conditions, while chocolate blood agar was incubated in an 8% CO 2 atmosphere.…”
Section: Bacterial Cultivation and Isolation Of A Pleuropneumoniaementioning
confidence: 99%